The Influence of Leadership Style On Employee Work Productivity Through Work Motivation And Job Satisfaction At PT PCS International - Ryan Sevllera; Zainul Kisman (CV. Picmotiv, 2026)
This study aims to analyze the influence of leadership style on employee work productivity by considering the mediating roles of work motivation and job satisfaction at PT PCS International. The background of this research is based on the observed decline in the company’s work productivity index, which decreased from 87.20 in 2022 to 86.00 in 2023 and further to 84.80 in 2024. This study employs a quantitative approach using path analysis techniques to examine the relationships among the research variables. The results indicate that leadership style, work motivation, and job satisfaction have significant effects on employee productivity, both directly and indirectly. These findings provide an important basis for organizations in designing strategies to enhance productivity through effective and targeted human resource management.